IMPACT OF HUMAN ACTIVITIES ON COASTAL VEGETATION - A REVIEW - Calvã o, Teresa; Pessoa, Maria Fernanda; Lidon, Fernando Cebola (Emirates Journal of Food and Agriculture, 2017)
Coastal dunes constitute complex interface ecosystems between the land and sea, providing important ecological and socio-economic services like coastal protection, recreation, regulation, food supply and biodiversity. They are characterized by high ecological diversity and also by extremely specialized and endemic species. Coastal areas, because of their position between land and sea, are attractive for many human activities. Unfortunately coastal systems have had a long history of exploitation and mismanagement.